A Civil Society The Public Space of Freemason Women in France, 1744-1944 - Allen, James Smith (University of Nebraska Press, 2021)
"James Smith Allen explores the two-hundred-year struggle to initiate women as full participants in the masonic brotherhood that shared in the rise of France's civil society and its "civic morality" on behalf of women's rights. "